Economic impact of the attendees to the Winter Universiade 2015 in the city of Granada - Roca-Cruz, A.; González-Ruiz, J.; Porcel-Rodríguez, P.; Cabello-Manrique, D. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
Mega-sport events create a new image of the host country, attracting viewers and the media (Santo, 2005; Cornelissen and Swart, 2006). The economic impact of an event can be defined as the net economic change in the host country that derives from the expenditure attributed to the event (Crompton, 1995). Since one of the most important benefits are the permanent benefits in the city (Witt, 1988) as the improvement of the facilities or the image of the country. In relation to the tourism of a big event there is a moderate increase of the internal business tourism in a city during the development of the event (OECD, 2012). Thus, the city increases its investment potential and commercial activity (Avison Young, 2003). The objective of the present study was to analyze the economic impact generated by the attendees in the city of Granada during the Universiade Granada 2015.